“Somebody has to be crazy about that kid”: Speculating on the transformative recordkeeping potential of the caring corporate parent - Ballin, Mya (Archival science, 2024)
Just as archival scholarship has increasingly engaged in conversations around care and holistic considerations of the agency of records subjects, the child welfare systems of the modern Western world have been moving towards conversations that aim to centre and celebrate the voice of the child in new and important ways. However, too often are these conversations held back by the enormity of the issue and the overhaul that would have to take place for philosophy to match with practice. In this paper, I suggest that part of the problem is that we have been trying to make these changes philosophy first, placing a new way of thinking on top of an old way of doing—an approach that will never generate change. Leaning in to using speculation to imagine what the new recordkeeping of a caring system might look like, I propose that the act of recordkeeping is the fulcrum that could make caring child welfare a reality and illustrate some of the avenues through which we might pursue instigating the systemic changes needed if we are to see the agency and perspectives of children prioritised in child welfare and protection practices.